Aplikasi Survei Kerawanan Pemilu Berbasis Web Menggunakan Metode SDLC - Valian Yoga Pudya Ardhana; M. Dermawan Mulyodiputro; Lilik Hidayati (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Election vulnerability refers to the potential for interference, fraud, or threats to the integrity and democratic process in a general election. This can include certain variations such as vote manipulation, voter intimidation, misuse of state resources, as well as other legal violations that can affect the fairness and validity of election results. The solution to overcome vulnerabilities in elections is to use a survey application. The existence of an election vulnerability survey application is an effort to obtain more accurate and faster data and information regarding vulnerabilities in the implementation of general elections (elections). The election vulnerability survey application is a tool that helps minimize the risk of insecurity and improves the integrity and quality of elections in implementing democratic principles. By using this technology and application, it is hoped that monitoring and supervision of election vulnerabilities can be carried out more effectively and efficiently. The information collected can be processed quickly and accurately, so that it can provide. Testing the questionnaire involved 10 admins and respondents who were surveyors and respondents who would be surveyed and it was found that this election vulnerability survey application had been tested well and was successful.